A 6-week randomized-controlled field study: effect of isokinetic eccentric resistance training on strength, flexibility and muscle structure of the shoulder external rotators in male junior handball players - Vetter, S.; Witt, M.; Hepp, P.; Schleichardt, A.; Denecke, T.; Köhler, H.-P. (Frontiers in Physiology, 2024)
Background: Team handball involves a tremendous amount of shoulder motion with high forces during repeated extended external range of motion. This causes shoulder complaints and overuse injuries. While eccentric training for the lower extremity shows preventive effects by improving strength, range of motion and fascicle length, there is a research gap for the shoulder joint and for advanced tissue characterization using diffusion tensor imaging.